Controlled grafting superhydrophobic cellulose surface with environmentally-friendly short fluoroalkyl chains by ATRP. (15th November 2015) - Li, S.H.; Huang, J.Y.; Ge, M.Z.; Li, S.W.; Xing, T.L.; Chen, G.Q.; Liu, Y.Q.; Zhang, K.Q.; Al-Deyab, S.S.; Lai, Y.K.
Abstract: Short fluoroalkyl chain of C3 F7 instead of longer fluoroalkyl chain (C > 7) was robustly grafted on cotton fibers via an atom transfer radical polymerization (ATRP) strategy. This study focused on the influence of different finishing parameters (synthetic approach, grafting concentration) and post-treatment (washing, drying) conditions on wettability, liquid adhesion, air permeability, and mechanical (dry abrasion and wet laundering) properties. The results indicated that C3 F7 chain was successfully grafting by a developed ATRP technique to construct superhydrophobic cotton fabrics. The optimized surfaces demonstrated super-anti-wetting property with a contact angle of about 163.7 ± 2.5° and an ultralow droplet adhesion of 62.3 ± 2.6 μN. The wettability remained highly hydrophobic even after 40 abrasion or 35 laundering cycles. This work also demonstrated the rational design and elaboration strategy of short fluorine-containing chains are vital for the construction of super-anti-wetting surfaces with controllable droplet adhesions. The results indicated that the anti-wetting, abrasion and laundering properties are much more influenced by the grafting strategy. We believe that environmental-friendly short fluoroalkyl chain (C < 4) can also be utilized for the construction of cotton fabric with good anti-wetting property and potentially applied in some practical fields, e.g., anti-wetting/icing outdoor cloth or self-cleaning sport textile. Graphical abstract: Highlights: Environmentally-friendly short fluoroalkyl chains (C3 F7 ) were grafted cellulose to obtain superhydrophobic cotton fabrics with controllable and high contrast adhesion. Repeated graft-on-graft strategy was developed to increase active spots for grafting. Excellent anti-wetting properties were combined with good abrasion and laundering stability.